Prikaz medpredmetnega povezovanja na primeru implementacije sodobne umetnosti v osmi razred osnovne šole - Kozjek Varl, Katja; Duh, Matjaž (Revija za elementarno izobraževanje, 2017)
Cross-curricular Integration in the Case of Contemporary Arts Implementation in the Eighth Grade of Primary School. The article presents a case involving implementation of contemporary visual arts in the teaching of arts in the eighth grade of primary school. In the research process we were primarily interested in a range of approaches (in three steps) that prepared students for learning and understanding contemporary visual arts. The last step involved the crosscurricular integration of subjects in order to meet the learning objectives of the school subjects involved. Students expressed their attitudes towards everyday situations through creative artistic work. Varied approaches in the planning and realisation of the artistic tasks posed a challenge for students in achieving creative artistic expression and shaping their own views of the given problem. Through the originality of ideas, the researched allowed us to perceive progress in creativity. At the same time, we also noticed increased student sensibility in experiencing and understanding certain contemporary artworks.
Keywords: contemporary visual arts; art education; authentic artwork; homeland and civic culture and ethics; elementary school